Pengaruh Pendidikan dan Pelatihan dan Kompetensi Penyuluh KB Terhadap Kinerja Penyuluh KB Dengan Dukungan Organisasi Sebagai Variabel Mediasi Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Bekasi - Indri Purwanti Hapsari; Harry Indratjahyo; Muhammad Harri (Jurnal Ekonomi dan Industri, 2025)
This study aims to analyze the influence of education and training and competence on the performance of Family Planning instructors, with organizational support as a mediating variable at the Bekasi City Population and Family Planning Control Office. The research method used was a quantitative approach with path analysis techniques. The sample in this study consisted of 46 family planning instructors determined by simple random sampling. Data were collected through a closed-ended questionnaire using a Likert scale, supported by semi-structured interviews. The results showed that education, training, and competence had a positive and significant effect on the performance of family planning instructors. In addition, organizational support proved to be a significant mediating variable in strengthening the influence of education, training, and competence on performance